Analisis Penggunaan Media Video Pembelajaran Berbasis Teknologi di Era Digital - Egi Tri Saputra; Nadjwa Nabila Rachman; Neng Tysha Nur Mahardiyanti; Muhamad Rafly Permana Putra; Wildan Muzaki; Didik Aribowo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
In the digital era, advancements in information and communication technology have asignificant impact on education, especially regarding the use of technology-based learning media. The purpose of this research is to evaluate how technology-based learning videos can enhance the quality of the teaching and learning process. The research and development (R&D) method was used, with data collection techniques such as observation, surveys, and documentation. The research results show that the learning video material was very well received by the students, with a percentage of 89.2%. By combining engaging animations, visual elements, audio, and simulations, the learning video has the ability to enhance student activity and improve material comprehension. Because it can be accessed and reviewed according to the students' needs, this media also helps students in self-directed learning. However, there are still several obstacles that hinder its implementation. Some of these include limited technological infrastructure, limited internet access, and the digital skills of teachers. Therefore, teachers need to have more technological resources and digital skills to maximize the use of learning videos. According to this study, technology-based learning videos are a useful innovation for improving the quality of education in the digital era.